Prerequisites for implementing security measures at the airport - Соловйова, О. О.; Валько, А. М. (Science-based technologies, 2020)
Thefieldofcivil aviation has achieved significant development in recent years. However, this development is aimed not only directly at improving air transport but also at aviation services. Due to this, the popularity of air travel has increased and at the same time, the passenger traffic of airports has also increased.The article provides an overview of the analysis of the development of the aviation industry and investigates the level of aviation security over the past 5 years. It is confirmed that all the above changes in the development of air transportation have a direct impact of a number of external factors on the state of trust of air passengers in the level of safety of air transportation.The presented changes in the indicators of aviation incidents confirm the need for constant monitoring of the system of measures to ensure aviation security. Despite the fact that the perfection of civil aviation facilities protection systems is determined by their quality according to the relevant indicators based on the criteria for choosing the best combinations of influencing factors. The necessity of considering alternative options for identifying signs of UIA preparation. One of the promising approaches to this problem is the introduction of profiling technology into the work of security services and law enforcement agencies, which at the state level has a small percentage in the airport system. It has been established that the effectiveness of aviation security depends on the implementation and compliance with the current legislation, and security procedures should be applied taking into account the mentality, gender, age of the subjects, which affects the quality and the speed of their implementation. It has been established that the effectiveness of securing of aviation security depends on the implementation and compliance with the current legislation, and security procedures should be applied taking into account the mentality, gender, age of the subjects, which affects the quality and the speed of their implementation. In turn, responsibility for airport security and all its facilities should be clearly established, understandable at all levels of controlled organizations and departments.